Pengembangan Model Permainan SRD (Spider Run Dance) Dalam Pembelajaran Kebugaran Jasmani - Dharmawan, Dhimas Bagus (Department of Physical Education, Sport, Health and Recreation, 2016)
This study aims to produce a model of game development is a model game SRD (Spider RunDance) in learning physical fitness of students in class VIII Public Junior High School 1 DukuhturiTegal. This research method is the development of research which refers to the modelof development of Brog & Gall. Results of this research is the data validation expert on earlyproduct before tested a small scale, on a small scale and large scale mean that the assessmentresults, the expert Penjas 80.87% (good) and learning experts 82.19% (good), from small scaletrial results of the questionnaire obtained an average percentage of 84.99% correspondingresponse (good). As for large-scale testing of the questionnaire results in the average percentageof answers according to 89.79% (good). Based on the above results, it can be concluded that themodel of the game SRD (Spider Run Dance) can be applied to class VIII Public Junior HighSchool 1 Dukuhturi and is recommended for teachers PJOK SMP Negeri 1 Dukuhturi thatmodels this game can be an alternative delivery of learning physical fitness with the expectedlearning model of this game will be more recreational and attractive.